Instability intervals for Hill’s equation with symmetric single-well potential - Başkaya, E.; Coşkun, H.; Kabataş, A. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.9 We deduce some explicit estimates for the periodic and semiperiodic eigenvalues and the lengths of the instability intervalsof Hill’s equation with symmetric single-well potentials by using an auxiliary eigenvalue problem. We also give boundsfor the gaps of the Dirichlet and Neumann eigenvalues.